A Measurement of radiation dose received by the thyroid organization on shoulder joint examination i: Measurement of radiation dose received by the thyroid organization on shoulder joint examination i - ARTITIN, CICILLIA (JURNAL TERAS KESEHATAN, 2024)
One of the examinations in the radiology installation is the Shoulder Joint, where a sensitive organ close to the examination is the thyroid. If the thyroid organ absorbs too much radiation, it causes the effects of thyroid cancer and thyroid tumor. This research aims to determine how the dose received by the thyroid and whether the dose received exceeds the prescribed dose limit value. The type of research is a quantitative done at the installation radiology of Ibnu Sina Islamic Hospital Padang on 5 August 2021. The method is an experimental study, using ten samples with raysafe measuring instruments. Then the data is processed using the effective dose formula and displayed in tabular form. The results obtained in the form of absorbed dose are then converted into equivalent doses by switching the absorbed dose to the radiation weight factor. Furthermore, the equivalent dose is multiplied by the weight factor